Change Management and the Human Factor Advances, Challenges and Contradictions in Organizational Development - Dievernich, Frank E. P.; Tokarski, Kim Oliver; Gong, Jie.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Change management and organizational development is unthinkable without people. Human beings form its core as both subjects and objects of change. This volume attempts to cut through to the core of change management, to the people that stand at its heart and focuses on their intrinsic role in change management and organizational development. Topics covered in this volume encompass the human element within organizational change, how this impacts roles, dynamics of team interaction and affects the workplace in teaching and learning settings. It also addresses resistance to institutional and organizational change and the central role that agile management plays in this process.
At the Heart: Human Beings in Organizations -- The Rediscovery of the Human Being and the Future of Change Management -- The Human Role Within Organizational Change - A Complex System Perspective -- Looking Through Someone Else's Eyes: Exploring Perceptions of Organizational Change -- The Role of Management Development in Change Management: The Example of Financial Markets -- Cultural Change by Speech: Team Learning and the Role of Interaction -- Strengthening Leader's Impact and Ability to Manage Change Through Group Coaching -- Implementing Strategy Means Changes for Employees -- Successful Organizational Change Through Overcoming Risks -- Resistance to Institutional and Organizational Change: An Individual Perspective -- Organisational Change and Workplace Stress in Teaching and Learning Settings: Case Study Evidence from a Public Sector University in the UK -- Organizational Development in an International Context: A Story of Planned Change and Attempt to Induce High Involvement -- Agile Management for Organizational Change and Development -- Challenging Notions of "Change" and "Change Management" -- Strange Encounter: An Inquiry into the Popularity of Participation in Organizations -- Leadership and Transformation.
Keywords: Business; Organization; Planning; Personnel management; Economic sociology; Industrial psychology; Business and Management; Organization; Organizational Studies, Economic Sociology; Industrial, Organisational and Economic Psychology; Human Resource Management; Electronic books